Analysis of Activity Planning In the 2765 Dwt Tanker Repair Process Using the Critical Path Method (Cpm) - Ach Alfan Shahri; Soffiana Agustin; Fahmy Ardhiansyah (Indonesian Vocational Research Journal, 2022)
Ships are basically a means of sea transportation, which connects an island or between regions of a country, which is used as passenger transportation, as well as transportation of goods. As the largest archipelagic country in the world, Indonesia has waters with two vast seas which are larger than the land. Therefore, sea transportation has an important role for the sustainability of the economy in Indonesia, so the need for developers in the maritime sector needs to be increased, one of which is in the field of Shipyards. In the ongoing docking process, it is necessary to schedule the work. So that the project runs in a structured manner, it is necessary to pay attention, because scheduling a project itself helps to detail the activities of an activity, the time required for project completion so that the project is on time Completion and there are no delays in workmanship Critical path method (CPM) itself is a method for identifying completion in a project to complete the completion of a project so that it is on time. And the authors use this method to help resolve and compare between the 2765 dwt tanker scheduling made by the shipyard and using the critical path method (CPM). The results of my research entitled " analysis of activity planning in the 2765 dwt tanker repair process using the critical path method (cpm) " are. The schedule made by the shipyard gets a completion time of 61 days, whereas if you use the critical path method, it takes 48 days.